AN ANALYSIS OF STUDENTS’ EXTERNAL FACTOR IN INFLUENCING VOCABULARY OF WRITING AT SMA MUHAMMADIYAH BANDAR LAMPUNG - M Agung Laksono; Yanuarius Yanu Dharmawan (LINGUISTIKA, 2017)
This research aimed to know what external factors improved students’ vocabulary and how external factor could give influence students in improving their vocabulary at SMA Muhammadiyah Bandar Lampung. This research was qualitative method which used triangulation method – observation, questionnaire, and interview. The researcher also gave activity to make a free writing. Students could tell story about their life. The result of students’ writing was used to prove the result of observation, questionnaire, and interview. The result showed that social factor was chosen by most students. Social factor was also one of external factors that had validity and reliability. It meant that social factor could give influence to students’ vocabulary. On the other hand, the result of interview also showed the students’ answer. There were different opinions between students and other students. The differences showed good relation between their answers and their score in writing activity. Based on the result, the researcher could conclude that the role of friends and teacher as external factor could influence students’ vocabulary.